Evaluating the technetium-99 m pertechnetate flow protocol for Graves’ disease: methodological insights: a case series - Jaber Abdulwahab Asiri; Rami Abdullah Alghamdi; Ahmed Ali AlRizqi; Shahad Khalaf Alrasheed; Abdulaziz Alaythan; Bander Mukhlef Alshammri; Mohammed Abdullah Alshehri; Mohammed Hadi Alarjani; Zyad Alshehri; Nahed Nasser ALFawaz; Rayan Saad Albalawi (Journal of Medical Case Reports)
Abstract Background Graves’ disease is the most prevalent cause of hyperthyroidism globally, with technetium-99m pertechnetate widely utilized in its diagnosis. Dynamic scintigraphy using technetium-99m pertechnetate has shown promise for early detection of Graves’ disease, particularly in subclinical presentations, but lacks standardized evaluation. This study aims to explore the utility of a dynamic technetium-99m pertechnetate scintigraphy protocol in hyperthyroidism, focusing on its diagnostic advantages and potential clinical applications. Case presentation The cases described involved adult male and female patients aged 34–40 years of Saudi Middle Eastern ethnicity. Conclusions Dynamic flow imaging using technetium-99m pertechnetate represents a promising diagnostic approach for Graves’ disease, particularly in challenging subclinical cases. This protocol has the potential to refine diagnostic accuracy and guide treatment decisions. Further validation through larger studies is warranted to establish its clinical utility.